Long Term Rainfall Trend of The Brantas Catchment Area, East Java - Edvin Aldrian; Yudha Setiawan Djamil (Indonesian Journal of Geography, 2006)
Spatial and temporal rainfall analyses of the Brantas Catchment Area from 1955 to 2002 based on 40 daily rainfall stations has been performed. To identify the climate pattern for the last five decades, we used the Empirical Orthogonal Function (EOF) followed by the Fast Fourier Transform. By using EOF, we found the monsoonal pattern as the most dominant, which explains about 72% of all variances. The interannual pattern shows a negative trend of the monsoonal strength. From the monthly isohyets for each decade, the rainfall amount appears to decrease significantly during the last five decades, indicated by wider low rainfall amount areas and the orographic effect is detected, indicated by always greater amount in highlands. From rainfall data in mountain and coastal areas, dry periods had been increasing, mainly in lowlands. Thus, the continued imbalance of the dry and wet period is one cause of the monsoonal strength decrease during the last five decades.